Greek Physicians’ Perceptions on Generic Drugs in the Era of Austerity - Georgios Labiris; Michael Fanariotis; Catherine Kastanioti; Georgios Alexias; Adonis Protopapas; Theodoros Karampitsakos; Dimitris Niakas (Scientifica)
Purpose. To assess the beliefs and preferences of Greek physicians, regarding generic drugs, in the years of financial crisis. Setting. Multicentered, nationwide survey. Material and Methods. A custom questionnaire based on former similar studies was developed and administered to Greek physicians. The variable “perception on generics” was constructed after an exploratory study and the instrument was validated by conventional and Rasch analysis methods. 22 items formed 5 subscales that constructed the variable in question. Results. 908 physicians successfully participated in the study (response rate: 80%). Mean total scores to the instrument were 60.63 ± 12.12 for men and significantly less (58.24 ± 11.73) for women (p = 0.04). Greek physicians were not persuaded on the potential economic gain (45.79 ± 10.53); moreover they identified that Greek authorities cannot address the increased pharmacovigilance mandates. Physicians working in Athens and those working in surgical units demonstrated significantly worse scores than their colleagues from the rest of Greece and those working in Internal Medicine wards (p = 0.03).  Conclusion. Our results suggest an overall poor acceptance of the national initiative on generic drugs by Greek physicians. This trial is registered with Clinicaltrials.gov identifier: NCT01855802.